An innovative approach to treating vaginal mesh exposure after abdominal sacral colpopexy: endoscopic resection of mesh and platelet-rich plasma; initial experience in three women. (February 2017) - Castellani, Daniele; Valloni, Alessandra; Piccirilli, Angela; Paradiso Galatioto, Giuseppe; Vicentini, Carlo
Abstract Introduction and hypothesis Polypropylene mesh exposure is uncommon after abdominal sacral colpopexy (ASC), but in case of symptomatic vaginal mesh exposure, surgery is needed. When treating it, care must be taken to completely remove the exposed mesh (EM), saving as much vaginal tissue as possible to avoid a subsequent shortened and narrowed vagina. In this video, we present a minimally invasive technique for treating EM after ASC using endoscopic mesh resection and autologous platelet-rich plasma (PRP) technology. Methods Three women were referred to our outpatient clinic for vaginal vault mesh exposure after laparoscopic ASC with concomitant hysterectomy. All women underwent endoscopic bipolar PlasmaKinetic resection (BPR) of EM, and PRP gel was delivered in the surgical site to cover the gap left by the resection. Results Mean operative time was 39.6 min. Surgery was uneventful in all cases. All women recovered sexual function, and nobody experienced relapsed pelvic organ prolapse at 1-year follow-up. Conclusions Our preliminary results show that BPR and PRP are safe, effective, and feasible for treating vaginal mesh exposure with conservation of anatomy and sexual function.